(untitled) (Research, Society and Development, 2024)
Immunotherapy has emerged as a revolutionary approach in cancer treatment, offering new hope for patients with previously intractable types of cancer. This article reviews recent advances in immunotherapy, highlighting key developments and their clinical implications. The review covers immune checkpoint inhibitors, chimeric antigen receptor T-cell (CAR-T) therapies, therapeutic cancer vaccines, and the combination of immunotherapies with other treatment modalities. Checkpoint inhibitors, such as anti-CTLA-4 and anti-PD-1/PD-L1 antibodies, have shown significant efficacy in various cancers, including melanoma and non-small cell lung cancer. CAR-T cell therapies have shown promising results in hematologic cancers, while therapeutic vaccines have the potential to induce robust and durable immune responses. The combination of immunotherapies with chemotherapy, radiotherapy, and targeted therapies is being explored to enhance efficacy and overcome treatment resistance. Despite the advances, significant challenges remain, including treatment resistance and side effects. Continuous research is essential to better understand the mechanisms of action of immunotherapy and develop new strategies to overcome current challenges. With the advancement of science and technology, immunotherapy has the potential to become an increasingly effective and widely used therapeutic approach in cancer treatment.